Ethical Attitudes of Accounting and Business Students: Malaysian Evidence - Yahaya, Rusliza; Zainol, Zuraidah; Ahamad Rapani, Norhanani; Mat Norwani, Norlia; Samsudin, Norsamsinar; Mat Jizat, Jessnor Elmy (International Business Education Journal, 2016)
Ethical crises in business have gained more attention from public and have led many to question the effectiveness of ethics education in university. Therefore, this study was designed to investigate the ethical attitudes of accounting and business students, their willingness to become whistleblowers, and the impact of ethics education on students’ ethical attitude. A total of 275 usable questionnaires that consists of four ethical scenarios were analysed. The findings of the study show that a small percentage of accounting and business students are willing to involve in unethical behaviour. About 10.9% of students were categorized as unethical as they would cheat in an examination and that only 1% of the students would accept bribes to defraud the tax office. Once an element of risk of being caught was introduced, the percentage of students willing to cheat in an examination and those willing to defraud the tax office decrease to 4.8% and 0.7% respectively. The finding also shows that once the penalty was introduced, the number of students who would act unethically decrease and the number of those who would act as whistle blowers increase. In general, the students are willing to become whistleblowers. The majority of accounting and business students who discovered fraud and decided not to participate are willing to report the case to relevant authorities. However, the findings indicate no significant relationship between ethics courses and ethical attitudes of students.